Editorial: Protein post-translational modifications in the nervous system: from development to disease and ageing - Alvarez, Beatriz; Symmank, Judit; Zimmer-Bensch, Geraldine; Diaz-Hernandez, Miguel; Franzka, Patricia (Frontiers in Molecular Neuroscience, 2024)
Graphical AbstractPTMs are crucial for biological processes contributing to healthy organ function. Protein post-translational modifications (PTMs), such as phosphorylation (P), acetylation (Ac), SUMOylation (SUMO), S-nitrosylation (Nitro), ubiquitination (Ub) and glycosylation (Glyco), affect a wide range of cellular and biological functions as depicted in this cartoon. Perturbations lead to severe consequences for the normal function of the brain and other organs, such as muscle. Created in BioRender. Hübner (2024) BioRender.com/j49w898.